Characteristic basis function method based on mixed discretization for analyzing scattering from electrically large inhomogeneous objects. Issue 3 (11th February 2022) - Huang, Fei; Sun, Yufa
Abstract : The characteristic basis function method (CBFM) based on the mixed discretization (MD) is firstly proposed to analyze the electromagnetic scattering from electrically large inhomogeneous objects. The discontinuous Galerkin volume integral equation (DGVIE) method which employs nonconformal discretization permits to independently discretize the various component regions of the inhomogeneous object depending on its local shape or dielectric permittivity. Moreover, by the means of the CBFM, the low-level basis functions employed in the DGVIE method are converted into high-level basis functions, dramatically reducing the number of basis functions for modeling. In addition, the conformal discretization which is superior in dealing with homogenous regions is mixed with the nonconformal discretization to further cut down the number of the basis functions. Numerical results show that the CBFM based on mixed discretization (MD-CBFM) generates much less unknowns in contrast to several conventional methods. Several composite inhomogeneous examples are given to demonstrate the accuracy and efficiency of the proposed method.